Breastfeeding perceptions of first time mothers: A metaphor analysis - Durmuş, Ayşenur; Durmuş İskender, Mahinur; Coşkuner Potur, Dilek (Informa UK Limited, 2023)
Our purpose in the present study is to determine mothers' perceptions of breastfeeding through metaphors. This is qualitative, cross-sectional and descriptive study. The present study included 33 volunteer mothers who gave birth vaginally for the first time, received care in the postpartum service, and breastfed their babies at least 10 times. To reveal the metaphors related to the concept of breastfeeding, each mother was asked to complete the sentence "Breastfeeding is like… because…." The perceptions of the mothers about breastfeeding were gathered under three main themes: positive, negative and neutral metaphors. The identified metaphors were divided into five categories: indescribable emotion, peace, healing, task and inflicting pain. The mothers produced more positive metaphors about breastfeeding.
Keywords: Nursing (miscellaneous); Tıbbi ve Cerrahi Hemşirelik; Pharmacology (nursing); Nursing; Emergency Nursing; Sağlık Bilimleri; Critical Care Nursing; Clinical Medicine (MED); Nurse Assisting; Health Sciences; Maternity and Midwifery; İleri ve Uzman Hemşirelik; Klinik Tıp (MED); Asistan Hemşirelik; General Nursing; Advanced and Specialized Nursing; HEMŞİRELİK; Onkoloji (hemşirelik); Klinik Tıp; Genel Hemşirelik; Oncology (nursing); CLINICAL MEDICINE; Hemşirelik (çeşitli); Kadın Hastalıkları ve Doğum Hemşireliği; LPN and LVN; Acil Tıp Hemşireliği; Annelik ve Ebelik; Farmakoloji (hemşirelik); Gynecology and Obstetrics Nursing; Hemşirelik; LPN ve LVN; Yoğun Bakım Hemşireliği; Medical and Surgical Nursing; NURSING; 5. Gender equality